Pelatihan Digital Marketing Bagi Pemilik Rumah Kost Jalan Arung Sanrego Kota Makassar Menggunakan Piktochart: Digital Marketing Training for Boarding House Owners on Jalan Arung Sanrego, Makassar City Using Piktochart - A. Reski Almaida Dg Macenning; Hardiyanti Hatibu; Hasisa Haruna; Novi Wulandari; Rifhani Handayani L (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2024)
The rapid development of Makassar, particularly along the Arung Sanrego Street, has driven an increased demand for rental properties, particularly boarding houses, leading to intense competition among property owners. To succeed in this competition, an effective marketing strategy is required, one of which is digital marketing. This article aims to examine the application of digital marketing in the boarding house industry in Makassar, focusing on the utilization of digital platforms such as social media, websites, and property search applications. A training program was conducted for boarding house owners to enhance their understanding of digital marketing and the use of graphic design tools, such as Piktochart, to create attractive promotional materials. The results of the training showed a significant improvement in the participants' understanding of how to market their boarding houses effectively and efficiently, as well as expanding their market reach, even to other cities or provinces. Additionally, the training also had a positive impact on increasing the competitiveness of boarding house businesses, as owners were able to leverage data analytics to design more targeted marketing strategies. Overall, the implementation of digital marketing not only provides direct benefits to the boarding house owners but also contributes to the local economy through increased revenue and the creation of new jobs in the boarding house industry Keynote: Digitital Marketing, Piktochart,Kost